Workout intensity management standards for 6-7 year-old wrestlers - Abramova, T. F.; Golovachev, A. I.; Nikitina, T. M.; Polfuntikova, A. V. (Theory and Practice of Physical Culture, 2021)
Objective of the study was to offer workout intensity management standards for the 6-7 year-old wrestlers based on the energy mechanisms functionality and physical fitness tests and analyses.